PELATIHAN PEMBUATAN MEDIA AJAR DAN SIMULASI UJIAN ANBK BERBASIS DARING - Vittalis Ayu; Bambang Soelistijanto; Henricus Agung Hernawan; J.B. Budi Darmawan; Bernadeta Wuri Harini; Martanto Martanto (Universitas Sanata Dharma, 2022)
The education sector is one of the most impacted areas of the COVID-19 pandemic. Schools, which generally hold offline meetings, now have to transform into online sessions. With this pandemic, the teaching process must be